Combustion performance of hydrogen-enriched fuels in a premixed burner - ÖZDEMİR, MEHMED RAFET; YANGAZ, MURAT UMUT; ŞENER, RAMAZAN (TAYLOR & FRANCIS LTD, 2020)
Premixed burners have been widely used in many applications for both industrial and household appliances. For this reason, it is very important to enhance the combustion and emission efficiency of premixed burners because of their strong position in the global dimension. On the other hand, the addition of hydrogen to various fuels has been a research topic in the last decade due to its environmental and economic positive effects. In this study, the effect of hydrogen addition to different gaseous fuels at different rates has been investigated in a premixed burner. A numerical parametric study has been carried out using a commercial CFD code. The gaseous fuels namely; methane, propane, LPG and natural gas have been enriched by different hydrogen addition rates with a 10% increment. Moreover, the results of pure hydrogen have been presented. The results reveal that the combustion efficiency for all fuels has been affected positively with hydrogen enrichment except for certain gas compositions. Furthermore, this study has shown that the hydrogen addition in general, decreases the unburnt HC and CO emissions.
Keywords: Domestic burner; CFD; hydrogen addition; emissions; combustion; THERMAL EFFICIENCY; GAS-BURNER; EMISSIONS; METHANE; MECHANISM; CLIMATE; PROPANE; ENGINE; LPG